WO3 Rich in Oxygen Vacancies Through Ion‐Exchange Reaction for Enhanced Electrocatalytic N2 Reduction to NH3. Issue 4 (22nd December 2020) - Zhang, Junbo; Jiang, Cheng; Du, Yanqiu; Sheng, Lei; Huang, Xianli; Wang, Tao; He, Jianping
Abstract: Electrochemical route is an admirable strategy for N2 fixation to NH3, which can save more energy and reduce greenhouse gas emissions compared with the Haber‐Bosch process. However, it still suffers from extremely low ammonia yield for the lack of effective electrocatalysts and shows low Faraday efficiency due to competitive hydrogen evolution reaction (HER). Herein, we firstly synthesized needle‐like K0.33 WO3.16 (K‐WO3 ) by molten salt method, then K0.33 WO3.16 with surface defect structure (WO3 ‐OV) was successfully obtained through ion‐exchange of H + and dehydration process. An obvious absorption enhancement in the near infrared region exhibited in UV‐vis absorption spectra and a significant ESR signal at g=2.003 proves the existence of O vacancies. The abundant oxygen vacancies ensure that Faraday efficiency of WO3 ‐OV gets improved to 25.45 % at −0.3 V (vs RHE), much superior to K‐WO3 (FE: 9.33 %). It is worth noting that defect‐rich WO3 ‐OV also shows high electrochemical stability. Abstract : Rich in oxygen vacancies : The needle‐like K0.33 WO3.16 (K‐WO3 ) is directly synthesized by molten salt method. Then K0.33 WO3.16 with O vacancies (WO3 ‐OV) was successfully obtained through ion‐exchange of H + and a dehydration process. The O vacancies of WO3 ‐OV serve as the active site of NRR, which greatly improves the NRR performance. WO3 ‐OV with good stability is considered as a promising NRR catalyst and it can guide the reasonable design and application of tungsten‐based catalysts.